Struktur Intelektual Penelitian Organisasi Pengetahuan dan Artificial Intelligence : Analisis Bibliometrik pada Database Scopus Tahun 1977-2023 - Abi Rafdi Ramadhan; Tamara Adrian Salim; Frans Asisi Datang; Muhammad Prabu Wibowo (Perpustakaan Nasional, 2023)
Abstract The objective of this study is to identify the most contributing journal articles to the research on knowledge organization and artificial intelligence, as well as to comprehend the development of research in knowledge organization and artificial intelligence from 1977 to 2023 using bibliometric methods. The analysis employed citation analysis and co-word analysis applied to the Scopus database. The findings revealed 136 documents related to knowledge organization and artificial intelligence. Out of the 9 most influential documents, 3 studies stood out with significantly higher citation counts compared to others, surpassing 150 citations. The research identified three clusters as the focal points. The first cluster emphasized keywords such as knowledge representation, semantics, and ontology, while the second cluster centered on keywords like knowledge-based systems, expert systems, and decision making.